Criminal Law Enforcement Against Violation of Minimum Age of Marriage - Achmad Yustian Jaya Sesunan (Fakultas Hukum Universitas Lampung, 2020)
Pancasila as the ideology of the nation which contains values as a philosophy for the life of the nation and state where human values as a form of awareness of human attitudes and actions based on the potential of human conscience in relation to norms and culture in general, it can generally be said that humans free to do whatever he wants, one of which is to do marriage. However, marriage in early childhood has caused several factors including, losing the rights that he should have gotten since childhood. There are a lot of reports about child marriage in Indonesia and conflicting rules between the two Laws (Law), namely Law No. 23 of 2002 concerning Child Protection and Law No. 1 of 1974 concerning Marriage, this is the reason the author examines child marriage from two corners of the Act. In general, law enforcement of violations of the minimum marriage age from the formulation stage has been problematic where the Child Protection Act does not include the Marriage Law in the consideration given, the application stage how it can run optimally if the formulation stage is already problematic, as well as the execution stage how it can provide benefits if there are multiple interpretations. In the enforcement and implementation of child marriage rules even though the Child Protection Act cannot be obstructed even though it has been married according to the Marriage Law. The most fundamental obstacle to law enforcement lies in the inadequacy or incompleteness of the laws and regulations, so that there are many so-called